Formation of a policy of technological sovereignty in the territories of advanced socio-economic development by attracting private and public capital - N. S. Stepanov (Вестник университета)
The relevance of the article is due to the fact that the issue of sovereignty is now firmly rooted in digital space and manifests in many areas.   In particular, it is reflected in actions to relocalise production, support through the state, and attract investments.   The purpose of this study is theoretical substantiation of the directions in forming a policy of technological sovereignty in the zones of advanced socio-economic development with the help of private and public capital.   The following methods were used: comparative and logical analysis in studying of trends in the digital economy, synthesis and generalisation in determining the essence of technological sovereignty and formulating directions to improve these processes. The article gives reasons for the phenomenon being in fact an object of industrial policy, competition,innovative development, and geopolitical studies, which actualises the issue of its formation. Moreover, territories of advanced socio-economic development may become an effective mechanism in this case, as they have created favourable conditions to attract private and public capital. The research presents vectors of technological sovereignty establishment with consideration to the possibilities of a regional aspect (the mentioned territories) and an investment one (a combination of both types of capital).